STRATEGI PEMBERDAYAAN MASYARAKAT NELAYAN DI WILAYAH PESISIR KECAMATAN MARUSU KABUPATEN MAROS - Adi Sumandiyar; Hasruddin Nur; Abdul Muin; Darman Manda (Phinisi Integration Review, 2023)
This study aims to determine the success of empowering fishing communities in the coastal area of Marusu District, Maros Regency. The results showed that the implementation of empowering fishing communities in the coastal areas of Marusu District, Maros Regency was by creating instruments that regulate the empowerment of coastal fishing communities in order to optimize the quality of the coastal environment covering social, economic and cultural aspects as well as being able to create a conducive atmosphere for the implementation of development in in order to provide access to various interests of fishing communities to optimize development in coastal areas.Penelitian ini bertujuan untuk mengetahui keberhasilan pemberdayaan masyarakat nelayan di wilayah pesisir Kecamatan Marusu Kabupaten Maros. Hasil penelitian menunjukkan bahwa implementasi  pemberdayaan masyarakat nelayan di wilayah pesisir Kecamatan Marusu Kabupaten Maros adalah dengan cara membuat instrument yang mengatur pemberdayaan masyarakat nelayan wilayah pesisir agar dapat mengoptimalkan kualitas lingkungan pesisir melingkupi aspek sosial, ekonomi  dan budaya serta mampu menciptakan suasana yang kondusif bagi pelaksanaan pembangunan dalam rangka memberikan akses berbagai kepentingan masyarakat nelayan untuk mengoptimalkan pembangunan di wilayah pesisir.